Influence of local heat treatment of rivets on the joint formation of a versatile joining process - Kappe, Fabian; Bobbert, Mathias; Meschut, Gerson (IOP Conference Series: Materials Science and Engineering)
Abstract An efficient lightweight construction method is the combination of different materials in order to adapt the structure to the applied load. To join these multi-material structures mechanical joining technologies are applied. However, the rigid tooling systems cannot be adjusted to changing boundary conditions which is why new, versatile joining technologies are required. In the versatile self-piercing riveting (V-SPR) process presented in [1] different material combination are joined by using a multi-range capable rivet. The rivet head is formed onto the respective thickness of the joint by an outer punch. In order to punch thru the upper sheet a great rivet hardness is required whereas a lower hardness is required for the subsequent forming of the rivet head. To achieve a combination of these requirements, this study investigates a local heat treatment of the rivet. The aim is to determine the feasibility of such a heat treatment as well as to investigate the influence on the joint formation.